THE RELATIONSHIP OF SELF-EFFICACY AND WORK DISCIPLINE WITH EMPLOYEE PERFORMANCE - Nana Wahyuni; Muhamad Entang; Sufrin Hannan (Journal of Social Studies, Arts and Humanities (JSSAH), 2022)
The purpose of this study was to determine the relationship between self-efficacy and work discipline with employee performance. The study population was 282 employees and a sample of 166 employees. Data collection for each variable studied using a questionnaire with a grading scale. Data analysis techniques use descriptive statistical analysis techniques and inferential statistical analysis techniques. The results showed: (a) There is a positive and significant relationship between self-efficacy and employee performance with a correlation coefficient of ry. 1 = 0.773 and regression equation Å¶ = 37.263 + 0.814X1. The contribution of self-efficacy to employee performance was 59.75%, (b) There was a significant positive relationship between discipline and employee performance with a correlation coefficient of ry. 2 = 0.402 and regression equation Å¶ = 114.385 + 0.288X2, The contribution of discipline to employee performance by 16.16%, and (c) There is a significant positive relationship between self-efficacy and work discipline together with employee performance with a correlation coefficient of R = 0.804 and a regression equation of Å¶ = 20.546 + 0.756X1 + 0.163X2. The contribution of self-efficacy and work discipline together to employee performance was 41.21%